Short term consolidation of contaminated clay soil - Nur Azura, Karjanto (2014)
The petroleum industry's rapid growth causes several effects on the environment especially towards soil properties. This case puts a number of environmental and geotechnical problems from accidental spills of oil, leaking and its derivatives. Petrol, diesel and tars are examples of contaminant that affect the physical properties of the soil thus the consolidation and settlement too. In clay soils, contaminant diffusion is a significant process that impacts geotechnical and geo-environmental engineering systems. The chemical gives an influence on determining the performances of clay. The results indicated a increase in the coefficient of consolidation, cv and decrease in the coefficient of volume compressibility, mv, up to 6% oil content. There was great reduction in the amount of fines fraction with higher doses of contaminant by dry weight of soil. The percentage of clay size fraction in the uncontaminated soil was 84.79% and then reduced to 3.7 %, 0.5 1% and 0.2% when contaminated with contaminant content at 2%, 4% and 6% by dry weight of soil, respectively.